1975
DOI: 10.1090/s0002-9939-1975-0372461-3
|View full text |Cite
|
Sign up to set email alerts
|

Isolated points of the spectra of conservative matrices

Abstract: ABSTRACT. We show that the only possible isolated points in the spectrum of a conservative triangular matrix are its diagonal elements, and that any Hausdorff method corresponding to an absolutely continuous mass function is in the norm closure of the analytic methods.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

1984
1984
2012
2012

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…It then follows that f ∈ H(G), and f is continuous and bounded on G in C. Let σ(H µ ) denote the spectrum of H µ . Sharma [9] has shown that σ(H f ) ⊃ f (G). Either 0 ∈ σ(H f ) or 0 / ∈ σ(H f ).…”
mentioning
confidence: 99%
“…It then follows that f ∈ H(G), and f is continuous and bounded on G in C. Let σ(H µ ) denote the spectrum of H µ . Sharma [9] has shown that σ(H f ) ⊃ f (G). Either 0 ∈ σ(H f ) or 0 / ∈ σ(H f ).…”
mentioning
confidence: 99%